The Effect of Self-Concept on Student’s Mathematics Representation Ability - Rosi Fatmala; Fitria Zana Kumala (Jurnal Pendidikan Matematika, 2023)
Representational ability, namely the ability of students to express mathematical ideas in their minds into tangible forms such as pictures, tables, symbols, mathematical equations, writing or words, and so on. Self-concept is one of the variables that is considered to affect students' mathematical representation abilities. Self-concept is how he sees himself. The study aimed to investigate whether self-concept influences the mathematical representation abilities of Grade VIII students at SMP Negeri 9 Purwokerto. Quantitative methods were used in this study with a survey approach. The study population consisted of 283 class VIII students of SMP Negeri 9 Purwokerto, with a total sample of 166 students. The independent variable in the form of self-concept and the dependent variable in the form of students' mathematical representation abilities are the variables in this study. Questionnaires were used to assess self-concept, and tests were to assess students' mathematics representation ability. Data analysis was performed by simple linear regression. The research shows that self-concept has an influence of 18.2% on students' mathematical representation abilities, while other variables influence 81.8% of students' mathematical representation abilities. Based on the research that has been done, self-concept affects the students' mathematics representation ability of class VIII students of SMP Negeri 9 Purwokerto. The effect of self-concept on students' mathematics representation ability is 0.182.